The Role of Physical Exercise Intesity to Irisin Levels on Overweight and Obese - Abdulloh, Ido Nur; Sugiharto, Sugiharto; Rejeki, Purwo Sri (Folia Medica Indonesiana, 2021)
Highlight: • The differences in intensity physical exercise mechanisms associated with increased irisin secretion in overweight and obese subjects were determined. • The secretion of irisin in the right intensity blood on obesity can be reduced because the calories were balanced. Abstract: Physical exercise is a non-pharmacological therapy that can secrete various types of myokines to treat obesity problems. One of the myokines that play a role is irisin. Irisin is a polypeptide hormone with 112 amino acid residues that are synthesized in skeletal muscle after the proteolytic precursor cleavage of fibronectin type III domain-containing protein 5 (FNDC5). The release of irisin in the blood circulation will stimulate the browning process in white fat tissue by inducing the expression of uncoupling protein-1 (UCP-1) through signaling p38 mitogen-activated protein kinase (p38-MAPK) to increase energy expenditure, thermogenesis and reduce fat accumulation. This study described the differences in intensity of physical exercise mechanisms associated with the increased irisin secretion in overweight and obese subjects. This study was designed as a literature review that involved studies from research journals in the last 10 years concerning humans from some databases, such as Science Direct, PubMed, and Google Scholar. This study also discussed the relationship between the intensity of physical exercise and the synthesis, secretion, circulation, and regulation of irisin in preventing obesity.